"You do not understand ME": Hybridity and Third Space in Age of Iron - Severini, Giorgia (Theatre Research in Canada / Recherches théâtrales au Canada, 2010)
This paper discusses the 1993 play Age of Iron in relation to Homi K. Bhabha’s theories of hybridity and Third Space. It also examines the play through responses to Bhabha’s theories (including those by Britta Kalscheur, Smadar Lavie, and Ted Swedenburg), that argue that hybrid forms cannot necessarily subvert the cultural power structure of White and Other. Age of Iron acknowledges that hybridity alone is not enough to create a Third Space. This is evident in Clements’s Cassandra, a hybrid character who represents First Nations women abused at the hands of both white men and men of their own communities, and also fills the role of the Greek mythological prophet. This paper examines Cassandra’s journey as she seeks to have her experiences of abuse acknowledged and ultimately understands that she will not receive validation from her white oppressors. Résumé Cet article examine la pièce Age of Iron (1993) à la lumière des théories de l’hybridité et du tiers espace mises au point par Homi K. Bhabha. Il fait également appel à diverses réactions aux théories de Bhabha (dont celles de Britta Kalscheur, Smadar Lavie et Ted Swedenburg), qui font valoir que les formes hybrides ne réussissent pas nécessairement à renverser les structures culturelles de pouvoir du Blanc et de l’Autre. La pièce Age of Iron reconnaît que l’hybridité à elle seule ne suffit pas à créer un tiers espace. C’est ce que nous voyons chez la Cassandra de Clements, un personnage hybride qui représente les femmes des Premières nations victimes de mauvais traitements aux mains d’hommes blancs et d’hommes de la communauté à laquelle elles appartiennent, tout en jouant le rôle de prophète mythologique grec. L’article examine le parcours de Cassandra alors qu’elle cherche à faire reconnaître les mauvais traitements qu’elle a subis et qu’elle comprend par la suite que ses oppresseurs blancs ne lui accorderont jamais la validation qu’elle demande.